2015
DOI: 10.1210/jc.2015-2803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interrupting Children's Sedentary Behaviors With Activity on Metabolic Function: A Randomized Trial

Abstract: Interrupting sedentary time with brief moderate-intensity walking improved short-term metabolic function in non-overweight children without increasing subsequent energy intake. These findings suggest that interrupting sedentary behavior may be a promising prevention strategy for reducing cardiometabolic risk in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 37 publications
6
91
1
3
Order By: Relevance
“…While this association has been largely unexplored in children, one cross-sectional study reported that the accumulation of 5–10 min sitting bouts (i.e., defined as occasions of continuous sitting) was negatively associated with inflammatory markers (i.e., C-reactive protein) [15]. Thus, it is possible that the manner in which sedentary time is accumulated, rather than the total volume of sedentary time, may better explain associations between sedentary time and health outcomes in children and adolescents [16]. …”
Section: Introductionmentioning
confidence: 99%
“…While this association has been largely unexplored in children, one cross-sectional study reported that the accumulation of 5–10 min sitting bouts (i.e., defined as occasions of continuous sitting) was negatively associated with inflammatory markers (i.e., C-reactive protein) [15]. Thus, it is possible that the manner in which sedentary time is accumulated, rather than the total volume of sedentary time, may better explain associations between sedentary time and health outcomes in children and adolescents [16]. …”
Section: Introductionmentioning
confidence: 99%
“…According to them, the active movement of the childhood population to the school was much more due to the lack of another alternative means of transport than to the population's true awareness of the bene its of this type of movement. It is also known that children encouraged to perform daily walks of moderate intensity can perceive increased insulin and reduced glucose levels, as well as lower fat concentrations than children exposed to sedentary habits (25,26). In that sense, behaviors that are considered sedentary, such as watching television and playing videogames for more than two hours, talking on the phone and using the computer are associated with higher BMI and lower exercise levels (27).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that screen time is associated with enhanced adiposity [33], and insulin resistance [34]. Furthermore, it has been demonstrated that physical inactivity that is linked with high sedentary behaviors can lead to metabolic disorders such as insulin resistance [7]. In our study population, the total time spent in front of a screen (as measured by the questionnaire) was high (151 min on weekdays and 223 min on weekends), thus indicating that most children exceed the guidelines that recommend no more than 2 hours of recreational screen time per day [35,36].…”
Section: Journal Of Physical Activity Researchmentioning
confidence: 99%
“…Furthermore, excessive sedentary behaviors are associated with pediatric obesity and metabolic risks [6]. Recent studies have also shown that interrupting sedentary time with brief moderate-intensity walking can improve short-term metabolic function in children who are not overweight [7].…”
Section: Introductionmentioning
confidence: 99%